...Η Δημοκρατία δυσχερής; Η ανάπτυξη των μηχανισμών του "αντικομμουνιστικού αγώνος" 1958-1961 - ΣΤΕΦΑΝΙΔΗΣ ΙΩΑΝΝΗΣ Δ. (Μνήμων, 2011)
Borrowing its title from a sympathetic political biography of Greek statesman Constantine Karamanlis (by French author Maurice Genevoix), this study utilizes the private papers of a former deputy minister for Press and Information and a number of other primary and secondary sources in order to elucidate the psychological warfare and propaganda campaign which the Greek government waged against primarily its left-wing opponents during the late 1950s and early 1960s. In May 1958, the United Democratic Left (ΕΔΑ) and its allies were returned the second largest party in the Greek Parliament with almost a quarter of the national vote. Coming less than nine years after the end of the Greek Civil War, this success alarmed many a supporter of the re-elected Karamanlis government, including the Palace, the military and the United States agencies then active in Greece. At an early stage, the prime minister appeared convinced that the situation called for drastic action. In addition to occasional crack-downs on leftist activity, an extensive network of state agencies and non-state groups evolved with avowed aim to ‘combat communism’. Yet, after two years of organizational proliferation and various non-starters, the ‘operational responsibility’ for the co-ordination and implementation of the ‘anti-communist struggle’ passed to the trusted Army leaders. This operation culminated on the eve of the October 1961 elections. In the wake of Karamanlis’ third electoral victory, both ΕΔΑ, whose vote was severely curtailed, and the regrouped centrist opposition denounced the result as the product of ‘violence and fraud’. Available evidence points at a sustained campaign, authorized by prime minister Karamanlis, secretly funded by the state budget and orchestrated by government agencies. Its primary aim was, of course, to help suppress leftist influence but in the process it did much to improve the appeal of the ruling party. The security apparatus and extraordinary legislation inherited from the Civil War years was complemented by new agencies and a host of private groups which combined ardent anti-communism with more self-seeking aims. US agencies also offered know-how and material support. Public opinion was ‘cultivated’ through various channels, including the governmentcontrolled radio, the pro-government press and subsidized journalists (including foreign correspondents), freely distributed publications, theatre, cinema, plus mobile ‘information’ units which roamed the countryside – covertly operated by the Army whose role increased as the government anxiously sought tangible results. Proof of this campaign was presented by the Centre government which ruled in 1964-65 but was disputed by the right-wing opposition and Karamanlis himself, who denied any personal involvement. In the face of the evidence available, such disclaimers hold little water. The longer-term effects Karamanlis’ decision to directly involve the Army in what primarily was a political and ideological contest would become painfully apparent when officers seasoned in the ‘anti-communist struggle’ abolished constitutional rule and seized power in 1967.